A review of the effectiveness of current time– temperature regulations on pathogen inactivation during composting. Issue 5 (3rd September 2007) - McCartney, Daryl; Wichuk, Kristine M
Abstract : Pathogenic organisms can be present in all types of compost feedstocks. Since the infective dose for many of these organisms is very low, it is generally accepted that pathogens should be reduced to non-detectable levels. According to North American regulatory bodies (United States Environmental Protection Agency and Canadian Council of Ministers of the Environment), pathogen inactivation is expected to occur if all particles of compost maintain temperatures greater than 55 °C for at least 3 days. A literature review was conducted to examine whether compliance with these time-temperature conditions consistently resulted in production of pathogen-free compost products. Survival of pathogenic bacteria, protozoa, and helminths occurred in a significant number of studies, despite the prescribed time-temperature conditions apparently being met. It was hypothesized that this could either be the result of inadequate time-temperature requirements or of difficulties in ensuring that the time-temperature criteria are met by all compost particles.